Navigating Copyright for Libraries : Purpose and Scope - Coates, Jessica (2022)
Much of the information that libraries make available is protected by copyright or subject to the terms of license agreements. This reader presents an overview of current issues in copyright law reform. The chapters present salient points, overviews of the law and legal concepts, selected comparisons of approaches around the world, significance of the topic, and opportunities for reform, advocacy, and other related resources.